The Influence of Service Quality and Price Perspective on Customer Satisfaction Users of Transport Services Online Taxi Car in Makassar City - Mujahid Mujahid; Nasyirah Nurdin; Syamsul Riyadi; M. Rafiq Surya Madewa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Grab-Car is an online taxi service from GRAB which is currently very much needed by the public in the transportation sector to facilitate community mobility. The development of this application-based online taxi transportation business is very easy to use for the community, whenever and wherever the public can use online-based taxi transportation services. This study aims to see the effect of service quality and price perceptions on customer satisfaction using Grab-Car online taxi transportation services in Makassar City. The sample in this study is the people who live in the city of Makassar who have used the Grab-Car service. Data collection techniques are observations and questionnaires given to Grab-Car customers as many as 100 respondents. This research is a quantitative study using statistical methods using the IBM SPSS Statistics Version 25 application. Based on the results of statistical tests, it can be seen partially that service quality and price perceptions have a positive and significant impact on customer satisfaction using Grab-Car online taxi transportation services.